Symphony No. 2, Op. 24, By Robert F. Kurka (1921-1957): A Band Transcription - Schrader, George Jr (My University, 2019)
The need for this project stems from the lack of published compositions and biographical material on Robert Kurka. Given his short life it is no surprise that a lack of information exists; however, based on numerous awards and grants received in his final years his music deserves more recognition and intensive study. Adding a unique work to the band repertoire further broadens awareness for another compositional voice from the 1950s. A band transcription of Kurka’s Symphony No. 2 addresses this need by providing a work to explore his compositional language in a large wind band setting. Symphony No. 2 is a well-crafted work written at the peak of Kurka’s compositional maturity. It lends itself well for a band transcription because of its prominent wind writing. Presently, wind ensembles are limited to programming The Good Soldier Schweik Suite for chamber wind ensemble, and the band transcription of his Concerto for Marimba and Orchestra by Thomas Wubbenhorst. The transcription of Symphony No. 2 will be the first piece by Robert Kurka for a large wind ensemble. The stylistic differences from his other works will reintroduce Kurka’s music with new sounds for the band genre.
Keywords: Music; Music Composition